Label‐free quantitative comparison of cerebrospinal fluid glycoproteins and endogenous peptides in subjects with Alzheimer's disease, mild cognitive impairment, and healthy individuals. Issue 12 (December 2016) - Wang, Jingxin; Cunningham, Robert; Zetterberg, Henrik; Asthana, Sanjay; Carlsson, Cynthia; Okonkwo, Ozioma; Li, Lingjun
Abstract : Purpose: The goal of this study is to investigate putative molecular dynamic changes in cerebrospinal fluids (CSFs) collected from individuals with mild cognitive impairment (MCI) and Alzheimer's disease (AD) as compared to healthy controls. Experimental design: The CSF samples from 12 subjects comprised of four cognitively normal individuals and eight patients with MCI and AD, respectively. Two aliquots of each CSF samples (total 1 mL) of each participant are used for this study. Endogenous peptide separations are performed using 10 000 molecular weight cut‐off filters followed by LC‐MS/MS identification and quantitation while lectin‐enrichment chromatography is used to enrich glycoproteins in CSF followed by trypsin digestion and subsequent LC‐MS/MS for shotgun identification and label‐free quantitation. Results: Using an optimized submicrogram peptide separation with molecular weight cut‐off filtration and an in house‐constructed database, 645 peptides are identified. Glycoproteins are enriched by lectin affinity chromatography, resulting in 795 identified proteins. The discovery and alterations of proSAAS‐derived peptides and transthyretin are described and their roles in AD are discussed. Conclusions and clinical relevance: Comprehensive identification of endogenous CSF peptidome is achieved. Fifteen proteins are found to be differentially expressed among the three groups. The dynamic changes of transthyretin are reported for the first time.